Investigation of a set of abdominal openings and description of two species of Platyprosopus Mannerheim (Coleoptera, Staphylinidae, Staphylininae) - Santos, Paulo Roberto Rozales Dos; Moreno, Carlos; Caron, Edilson (Zootaxa, 2026)
Platyprosopini Lynch, 1884 comprises a single genus, Platyprosopus Mannerheim, 1830, whose species exhibit a nearly worldwide distribution. Members of the genus are consistently collected in proximity to rivers or other humid environments. In the present study, we describe two species, including one new species, and provide the first investigation of a set of openings on the abdomen of Platyprosopus. In both P. parallelus Sharp and P. metaxyus sp. nov., we observed three openings situated at the base of tergites and sternites. No internal reservoir was detected, but a reinforced muscular system associated with the openings was present, and a cluster of cells adjacent to the basal insertions is presumed to function in glandular secretion. Because the biology of the genus and the chemical composition of the glandular secretions remain unknown, the function of the openings cannot yet be inferred.